2009
DOI: 10.1111/j.1741-3737.2009.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

A Weak Embrace: Popular and Scholarly Depictions of Single‐Parent Families, 1900 – 1998

Abstract: The growth of single‐parent families constitutes one of the most dramatic and most studied social changes of the 20th century. Evolving attitudes toward these families have received less attention. This paper explores depictions of these families in representative samples of popular magazine (N = 474) and social science journal (N = 202) articles. Critical depictions of divorce plummeted between 1900 and 1998, a trend stemming not from any increase in favorable depictions but from the virtual disappearance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 29 publications
0
25
0
2
Order By: Relevance
“…She found that depictions of single parent families created due to divorce became increasing less critical over the 20th century; however, the same trend was not found for never-married single parent families. Specifically, Usdansky's (2009) results suggest that representations of never-married single parent families "were as likely to be critical [negative] at the century's end as they had been at its beginning in both magazines and journals" (p. 222). It is important to note that Usdansky (2009) did not explore how these depictions varied by the gender of the single parent.…”
Section: Societal Views Of Single Parents In Generalmentioning
confidence: 94%
“…She found that depictions of single parent families created due to divorce became increasing less critical over the 20th century; however, the same trend was not found for never-married single parent families. Specifically, Usdansky's (2009) results suggest that representations of never-married single parent families "were as likely to be critical [negative] at the century's end as they had been at its beginning in both magazines and journals" (p. 222). It is important to note that Usdansky (2009) did not explore how these depictions varied by the gender of the single parent.…”
Section: Societal Views Of Single Parents In Generalmentioning
confidence: 94%
“…Scholars in the United States and elsewhere suggest that scientifi c evidence is disregarded by advocacy groups, policy makers, and professionals for many complex reasons (Duncan, Edwards, & Alexander, 2010;Furstenberg, 2007). Each of these conditions is highly stigmatized (Landy, Sword, & Valaitis, 2009;Usdansky, 2009). Each of these conditions is highly stigmatized (Landy, Sword, & Valaitis, 2009;Usdansky, 2009).…”
Section: The Misrepresentation Of Teen Mothersmentioning
confidence: 99%
“…Following the developmental trends of Western industrialized countries (Cherlin 1992;Trent and South 1989;Usdansky 2009), economic growth, the prevalence of education, and an increase in female labor participation have contributed to the prevalence of divorce in Taiwan (Hsueh 2002). In addition, because young Taiwanese are more likely to be individualistic, criticism toward divorced parents appears to be lower in recent years.…”
Section: Divorce In East Asian Countriesmentioning
confidence: 99%